Why Businesses Should Experiment With Quantum Computing Now - Goldfarb, Avi; Teodoridis, Florenta (MIT Sloan Management Review, 2026)
Companies shouldn’t wait until quantum computing technologies have reached maturity to invest in them. As an enabling technology, quantum requires hands-on experimentation, feedback loops that support incremental learning, and co-invention cycles between producers and users — over time — to identify practical use cases. Investments in quantum today may see near-term payoffs, but the focus should be on active learning and the potential for breakthrough innovations over the longer term.